Too Far, Too Close: Religious Affiliations and Asians' Perceptions of US and China's Influence1. Issue 1 (21st August 2012) - Kim, Myunghee
Abstract : This article examines the impact of sociopolitical and spiritual factors on Asians' perceptions of US and China's influence. From the 2003 AsiaBarometer survey, seven Asian countries with diverse socioeconomic and religious components are analyzed—India, Japan, Malaysia, South Korea, Sri Lanka, Thailand, and Uzbekistan. Multilevel estimates reveal that (i) individuals from the seven nations show fewer similarities than do members of different religious institutions concerning US and China's influence in the region; (ii) only Muslims strongly oppose US influence in the region, while other religious affiliations do not wield any significant explanatory power. Contrastingly, individuals affiliated with religions positively perceive China's influence; (iii) sociopolitical contentment substantially boosts favorable perception about the United States and China; and (iv) spiritual perseverance discourages approval of the United States and China, but not trust in religious organizations.